2012
DOI: 10.1007/s10750-011-0992-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of rotifer assemblages in shallow waterbodies of semi-arid northwest Iran differing in salinity and vegetation cover

Abstract: Rotifers are important components of freshwater ecosystems and sensitive indicators of environmental changes. This study was carried out to test the hypothesis that, among environmental variables, salinity and aquatic vegetation have significant effects on rotifer diversity and abundance. We analyzed rotifer assemblages in the littoral zone of 22 hydromorphologically different shallow waterbodies in West Azarbaijan, Iran. Rotifer diversity and abundance were not significantly associated with basin morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…For instance, higher zooplankton species richness has also been associated with lower EC in temporary Mediterranean ponds and wetlands ( Waterkeyn et al ., 2008 ; Olmo et al ., 2016 ). Similarly to our study, salinity was one of the main drivers of rotifer community structure in a set of shallow water bodies comprising both permanent and temporal sites, with rotifer diversity significantly decreasing with increasing salinity ( Malekzadeh-Viayeh and Špoljar, 2012 ). In addition to EC, Pociecha et al .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…For instance, higher zooplankton species richness has also been associated with lower EC in temporary Mediterranean ponds and wetlands ( Waterkeyn et al ., 2008 ; Olmo et al ., 2016 ). Similarly to our study, salinity was one of the main drivers of rotifer community structure in a set of shallow water bodies comprising both permanent and temporal sites, with rotifer diversity significantly decreasing with increasing salinity ( Malekzadeh-Viayeh and Špoljar, 2012 ). In addition to EC, Pociecha et al .…”
Section: Discussionsupporting
confidence: 70%
“…Likewise, in the last decades, several studies have shown the importance of these habitats for biodiversity maintenance at the regional level ( Oertli et al ., 2002 ; Williams et al ., 2004 ; Davies et al ., 2008 ). Ponds are known to be sensitive to environmental changes ( Angeler et al ., 2010 ) such as salinity, temperature or macrophyte habitat structure ( Duggan et al ., 2001 ; Guisande et al ., 2008 ; Kaya et al ., 2010 ; Malekzadeh-Viayeh and Špoljar, 2012 ). They are also very vulnerable towards agricultural intensification and the associated fertilization and fragmentation of natural habitats, resulting in a loss of biodiversity ( Scheffer et al ., 2006 ; Céréghino et al ., 2008 ; Stoate et al ., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, no efficient filter-feeding cladoceran species were observed in the lagoons, possibly causing a weakening in the grazing pressure on phytoplankton and creating more eutrophic conditions. Several works in the literature confirmed that cladocerans are restricted to salinities below 3.5‰ (Frey, 1993;Viayeh and Špoljar et al, 2012). Furthermore, increase in salinity causes a decrease in their taxonomic diversity concurs with the present study, where high salinity during summer lowered the species richness in the lagoons.…”
Section: Discussionsupporting
confidence: 93%
“…They can be also abundant in coastal lagoons within a wide salinity range [e.g., 5 to 36 psu; Berre Lagoon, south of France, Mediterranean (Delpy et al 2012)], despite that it was demonstrated that this species shows high mortalities responding to high changes of salinity [>10 to 15 psu (Cervetto et al 1999)]. The role of salinity in shaping rotifer communities has also been demonstrated (Malekzadeh Viayeh and Špoljar 2012).…”
Section: Factors Controlling Zooplankton Communitymentioning
confidence: 99%